The Principle of Family Resilience in Islamic Law And Its Relevance to Cilegon’s Regional Regulation Number 1/2019 - Devika Rosa guspita; Ridwan, Ahmad Hasan; Khosi’ah, Siah; Solehuddin, Ending; Badriyah, Badriyah (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2025)
This study explores the application of family resilience principles within Islamic family law and its implications in Regional Regulation No. 1/ 2019 in Cilegon. The research adopts a qualitative approach, integrating legal analysis with field data from religious courts and local communities. This approach integrates normative legal analysis with empirical data obtained from field studies, including interviews with relevant parties such as religious court judges, traditional leaders, victims, and local communities. The findings suggest that the regulation establishes a legal framework consistent with Islamic principles, thereby enhancing marital stability and child custody arrangements. However, the study identifies challenges, including limited public awareness and legal disparities in implementation. A comparative analysis with similar regulations in Malaysia and Saudi Arabia suggests that Indonesia’s approach, while progressive, requires stronger enforcement mechanisms and enhanced educational outreach. The study concludes that effective integration of Islamic family resilience principles necessitates continuous legal refinement and policy adaptation.